2013
DOI: 10.1590/0001-3765201395412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the photodynamic activity of Xanthene Dyes on Artemia salina described by chemometric approaches

Abstract: The development of drugs for photodynamic therapy (PDT) is an important area of research due to their growing use in medical applications. Therefore, it is important to develop new bioassay methods for PDT photosensitizers that are inexpensive, easy to handle and highly sensitive to environmental conditions. Xanthene dyes (fluorescein, rose bengal B, erythrosine B and eosin Y) with LED light sources were investigated using Artemia salina as a bioindicator of photodynamic activity. In this study, three factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…34 Other authors have observed the same tendency in PDIMO applications of xanthene dyes for antibacterial applications. 35,36 Thus, the distribution of these dyes that we have proposed strongly supports these results concerning the high membrane penetration of RBB.…”
Section: Fluorescence Resonance Energy Transfermentioning
confidence: 56%
“…34 Other authors have observed the same tendency in PDIMO applications of xanthene dyes for antibacterial applications. 35,36 Thus, the distribution of these dyes that we have proposed strongly supports these results concerning the high membrane penetration of RBB.…”
Section: Fluorescence Resonance Energy Transfermentioning
confidence: 56%
“…Our interest in this compound stems from its known ability to function as a triplet state photosensitizer in water. Indeed, xanthene dyes , in general are promising sensitizers for antimicrobial studies , because of their relatively low toxicity, high triplet energies, near-quantitative triplet state quantum yields, and relatively long triplet lifetimes. The interest in killing bacteria by way of photodynamic therapy has led to further development of new sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…therapy (PDT) drug evaluation by photokilling of Artemia salina [11]. It also used as sensitizers for zinc oxide solar cells and the eosin yellow given a better results compared with the other used xanthene dyes [12].…”
mentioning
confidence: 99%